Exploring the scope and utility of peer observation by medical students: A narrative review - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Prithvi Brahmanand Petkar; Harshal Gajanan Mendhe; Ankit Kishor Badge (Wolters Kluwer Medknow Publications, 2024)
As medical knowledge continues to advance each day and there are multiple competencies that need to be acquired by undergraduate students, it becomes quite challenging for them to become competent within the period of training. The purpose of the current review is to explore the process of peer observation, identify the benefits attributed to peer observation, and explore various strategies to measure the impact of peer observation in medical education. An extensive search of all materials related to the topic was carried out on the PubMed and Google Scholar search engines and a total of 25 articles were selected based on their suitability with the current review objectives. Keywords used in the search include peer observation in the title alone only (viz. peer observation [ti] AND teaching [ti]; peer observation [ti] AND feedback [ti]; peer observation [ti] AND faculty [ti]; peer observation [ti] AND evaluation [ti]; peer observation [ti]). The approach of peer observation by medical students has been acknowledged as one of the important tools to improve the teaching and learning experiences by making everyone accountable. The success of peer observation in any medical college depends on the groundwork that has been carried out prior to its introduction. To maximize the benefit of peer observation in medical education for both stakeholders, we must take specific measures to conduct effective observations. In conclusion, peer observation by medical students is an effective approach to empower students as educators and develop a culture of continuous improvement in the institution. Acknowledging the merits of peer observation, the need of the hour is to adopt a systematic approach to ensure its successful planning and implementation in medical colleges.